Genetic shifts of Japanese encephalitis virus (JEV) in mosquitoes in the Republic of Korea, 2017-2022. - Bo-Ram Yun; Ji-Young Kwon; Byung-Eon Noh; Sehoon Cho; Dongmi Kwak; Hee Il Lee (PLoS Neglected Tropical Diseases)
Background The Japanese encephalitis virus (JEV) is transmitted by mosquitoes and circulates in Asia, the western Pacific, and other parts of the world. It is classified into five genotypes (GI-GV) based on the nucleotide sequence of the envelope (E) gene. Despite extensive surveillance, shifts in genotype distribution and mosquito species remain underreported, particularly in the Republic of Korea. Methodology/principal findings We conducted a nationwide mosquito collection from 2017 to 2022, capturing 1,102,031 mosquitoes from 32 sites nationwide. The predominant species were Aedes vexans (34.2%), Culex pipiens (17.9%), Cx. tritaeniorhynchus (13.4%), Ae. albopictus (4.0%), and Cx. orientalis (0.6%). JEV was detected in 49 pools, with the majority from Cx. pipiens and Cx. tritaeniorhynchus. Genetic analyses identified genotypes I, III, and V, with genotype V becoming dominant from 2020 onwards. Conclusions/significance The emergence of genotype V as the dominant strain of the JEV, along with its detection in mosquito species other than the previously known Cx. tritaeniorhynchus, highlights the need for ongoing surveillance. These findings underscore the importance of developing vaccines effective against all JEV genotypes to mitigate public health risks.